Dampak Personalisasi Konten di Media Sosial Terhadap Minat Menggunakan Jasa Pariwisata Melalui Keterlibatan Konsumen - Mirza Putri Andita; Azalia Mawarindani Indra (Jurnal Maksipreneur, 2026)
Leveraging AI to create relevant content for audiences facilitates genuine two-way communication, which can significantly increase customer engagement and, consequently, strengthen intention to use the service. This study investigates the direct and indirect effects of personalized content on intention to use, utilizing consumer engagement as a mediating variable. The research focuses on Indonesian consumers who have interacted with the local guide tour service provider @kawanceritaoutdoor. A quantitative approach was employed, collecting data from 150 respondents via an online survey; respondents were selected based on their interaction with @kawanceritaoutdoor's AI-personalized content on Instagram. The results show that personalized content significantly and positively influences consumer engagement and intention to use. However, consumer engagement does not significantly influence intention to use. Consequently, the study finds that consumer engagement does not mediate the correlation between personalized content and intention to use. The divergence from some previous research suggests that the specific type of interaction in consumer engagement is crucial in determining its effectiveness on buying decisions. This research provides practical insights to optimize content strategies aimed at building deeper connections with the consumer to effectively enhance purchase intention conversion.